2003
DOI: 10.1002/dvdy.10360
|View full text |Cite
|
Sign up to set email alerts
|

Epicardium is required for the full rate of myocyte proliferation and levels of expression of myocyte mitogenic factors FGF2 and its receptor, FGFR‐1, but not for transmural myocardial patterning in the embryonic chick heart

Abstract: Proper heart development requires patterning across the myocardial wall. Early myocardial patterning is characterized by a transmural subdivision of the myocardium into an outer, highly mitotic, compact zone and an inner, trabecular zone with lower mitotic activity. We have shown previously that fibroblast growth factor receptor (FGFR) -mediated signaling is central to myocyte proliferation in the developing heart. Consistent with this, FGFR-1 and FGF2 are more highly expressed in myocytes of the compact zone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 70 publications
7
114
0
Order By: Relevance
“…48,68,113,114 In mice, Fgf-9, Fgf-16, and Fgf-20 are expressed in epicardium in partially overlapping patterns starting at E10. 68 Fgf-9 mutant mice die at birth and show a hypoplastic left ventricle associated with weak CM proliferation.…”
Section: Fibroblast Growth Factormentioning
confidence: 99%
“…48,68,113,114 In mice, Fgf-9, Fgf-16, and Fgf-20 are expressed in epicardium in partially overlapping patterns starting at E10. 68 Fgf-9 mutant mice die at birth and show a hypoplastic left ventricle associated with weak CM proliferation.…”
Section: Fibroblast Growth Factormentioning
confidence: 99%
“…Microsurgical ablation of the proepicardium results in deficient formation of the epicardium, deficient coronary vasculature, and a severe growth defect of the compact layer myocardium called ''thin myocardium syndrome'' (41). Genetic ablation of several epicardial molecules not only affects the development of the epicardium and EPDCs but also causes remarkable growth defects of the compact layer myocardium (13,41,42). In the present study, we have found that epicardium-specific deficiency in ␤-catenin expression does not only disturb the development of EPDCs but additionally leads to hypoplasia of the compact layer myocardium and reduced expansion (ballooning) of the ventricles.…”
Section: Impaired Development Of Epdcs and Myocardial Growth Defectsmentioning
confidence: 99%
“…In addition to the myocardial cell themselves, signals from the epicardium to the myocardium play an essential role in ventricular wall compact zone expansion (Kreidberg et al 1993;Kwee et al 1995;Yang et al 1995;Chen et al 2002;Pennisi et al 2003), while neither endocardium nor neural crest has been implicated. The phenotype observed for SMRT −/− embryos was strikingly similar to the heart phenotype reported previously for Retinoid X Receptor ␣ (RXR␣) gene-deleted mice (Kastner et al 1994;Sucov et al 1994) that has been reported to be independent of RXR␣ expression in myocytes (Chen et al 1998;Tran and Sucov 1998;Subbarayan et al 2000b) but to require RXR␣ in the epicardium .…”
Section: Smrt Is Required In Cardiac Myocardiummentioning
confidence: 99%